2012
DOI: 10.1139/h11-135
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in oxidative capacity differ between locomotory muscles and are associated with physical activity behavior

Abstract: There is discrepancy in the literature regarding the degree to which old age affects muscle bioenergetics. These discrepancies are likely influenced by several factors, including variations in physical activity (PA) and differences in the muscle group investigated. To test the hypothesis that age may affect muscles differently, we quantified oxidative capacity of tibialis anterior (TA) and vastus lateralis (VL) muscles in healthy, relatively sedentary younger (8 YW, 8 YM; 21–35 years) and older (8 OW, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
86
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 56 publications
10
86
2
Order By: Relevance
“…These results provide strong new evidence that the current body of literature supports the hypothesis that the effects of age vary by muscle. It is likely that this difference across muscles is, in part, due to age-related differences in PA patterns, as suggested by Larsen et al (2012). It has also been suggested (Coggan et al 1990) that the lower maximal whole-body aerobic capacity of older adults, which results in day-to-day activities being performed at a higher relative workload, may be sufficient to result in training-like adaptations in some but not all muscles.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results provide strong new evidence that the current body of literature supports the hypothesis that the effects of age vary by muscle. It is likely that this difference across muscles is, in part, due to age-related differences in PA patterns, as suggested by Larsen et al (2012). It has also been suggested (Coggan et al 1990) that the lower maximal whole-body aerobic capacity of older adults, which results in day-to-day activities being performed at a higher relative workload, may be sufficient to result in training-like adaptations in some but not all muscles.…”
Section: Discussionmentioning
confidence: 99%
“…During locomotion, the tibialis anterior is recruited to a similar extent regardless of walking or running speed; conversely, recruitment of the vastus lateralis increases with speed (Cappellini et al 2006). As such, it has been suggested that higher intensity activities might be needed to preserve oxidative capacity in the KE; indeed, in vivo oxidative capacity in the vastus lateralis of older adults is significantly associated with daily minutes of moderate-to-vigorous PA (Larsen et al 2012). In contrast, DF oxidative D r a f t capacity may be preserved the by usual locomotory activities of healthy, community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations